IL (Interleukin)-15 Bridges Astrocyte-Microglia Crosstalk and Exacerbates Brain Injury Following Intracerebral Hemorrhage. Issue 3 (March 2020) - Shi, Samuel X.; Li, Yu-Jing; Shi, Kaibin; Wood, Kristofer; Ducruet, Andrew F.; Liu, Qiang
Abstract : Background and Purpose—: Microglia are among the first cells to respond to intracerebral hemorrhage (ICH), but the mechanisms that underlie their activity following ICH remain unclear. IL (interleukin)-15 is a proinflammatory cytokine that orchestrates homeostasis and the intensity of the immune response following central nervous system inflammatory events. The goal of this study was to investigate the role of IL-15 in ICH injury. Methods—: Using brain slices of patients with ICH, we determined the presence and cellular source of IL-15. A transgenic mouse line with targeted expression of IL-15 in astrocytes was generated to determine the role of astrocytic IL-15 in ICH. The expression of IL-15 was controlled by a glial fibrillary acidic protein promoter (GFAP-IL-15 tg ). ICH was induced by intraparenchymal injection of collagenase or autologous blood. Results—: In patients with ICH and wild-type mice subjected to experimental ICH, we found a significant upregulation of IL-15 in astrocytes. In GFAP-IL-15 tg mice, we found that astrocyte-targeted expression of IL-15 exacerbated brain edema and neurological deficits following ICH. This aggravated ICH injury in GFAP-IL-15 tg mice is accompanied by increased microglial accumulation in close proximity to astrocytes in perihematomal tissues. Additionally, microglial expression of CD86, IL-1β, and TNF-α is markedly increased in GFAP-IL-15 tg mice following ICH. Furthermore, depletion of microglia using a colony stimulating factor 1 receptor inhibitor diminishes the exacerbation of ICH injury in GFAP-IL-15 tg mice. Conclusions—: Our findings identify IL-15 as a mediator of the crosstalk between astrocytes and microglia that exacerbates brain injury following ICH. Abstract : Supplemental Digital Content is available in the text.